Production of blueberries in subtropical climate of altitude - Medeiros, José Gilberto Sousa; Biasi, Luiz Antônio; Bona, Claudine Maria de; Cuquel, Francine Lorena (Comunicata Scientiae, 2021)
Phenology and production potential studies are important to choose the cultivars more adapted to the climatic conditions of a region. The objective of this work was to evaluate the phenology, productivity and fruit quality of blueberry cultivars in subtropical climate of altitude, in three production cycles (2012/2013, 2013/2014 and 2014/2015). Eight cultivars from rabbiteye (Aliceblue, Bluebelle, Bluegem, Briteblue, Climax, Delite, Powderblue and Woodard) and two from highbush (Georgiagem and O'Neal) groups was evaluated. The experimental design was in randomized blocks with four replications and six plants per plot, with four useful plants. The beginning and the end of flowering, beginning and end of harvest, production, berry weight, berry size, pH, soluble solids, titratable acidity, ratio and skin color of blueberries were evaluated. The cultivars had flowering period from July to September, and concentrated harvest in November and December. ‘Bluegem’ presented the highest yields in the three evaluated cycles, reaching the production of 1215 g plant-1 in the third cycle. This cultivar also showed low acidity and high ratio. Berry size, pH and soluble solids contents were very close with some variations among the cultivars, in the three cycles evaluated. Coloring of the fruit presented few variations over the years of assessment. The most productive blueberry cultivar is the Bluegem, followed by cultivars Climax, Delite and Powderblue, of rabbiteye group, demonstrating better fit for cultivation in subtropical climate of altitude.